The possible effects of the eastern EU-enlargement on Croatia - a trade analysis - Dražen Derado (European Regional Science Association (ERSA), 2004)
Economic integration in Europe will have significant effects not only on participating countries, but also on countries remaining outside of the EU-structures. Starting from the theory of custom union and the trade creation and trade diversion effects, this paper tries to apply the theoretical inferences relating to the countries participating in economic integration to those countries which do not take part in it. The ex ante-analysis focuses mainly on long-term dynamic effects which follow from increasing export possibilities and advantages from economies of scale. Taking into account the foreseen dynamics of trade barriers elimination as well as the effects of trade liberalization so far, the paper estimates the expected effects of further trade liberalization and the adjustment costs arising from increased competition and changing pattern of specialization. In doing so, it makes use of the export similarity index and the methodology of intra-industry trade measurement. Key words: customs union, economies of scale, intra-industry trade, EU, Croatia
Keywords: 330; customs union; economies of scale; intra-industry trade; EU; Croatia